Development Strategy of Dark Tourism in Former Colonial Mine of Sawahlunto as Educational Tourism Destination - Camelia Amanda (CV Projurnal Mitra Publikasi, 2025)
This study aims to identify dark tourism development strategies in the former colonial mine of Sawahlunto and analyze its impacts on the community and environment. Dark tourism, which refers to visits to locations associated with death, tragedy, or dark events, has great potential as an educational tourism destination in Indonesia. The research method used was qualitative, with data collection techniques through in-depth interviews and participatory observation. The research subjects included relevant stakeholders and local communities. The results showed that dark tourism development strategies in Sawahlunto include effective marketing and promotion, development of adequate infrastructure, and training and empowerment of local communities. The impact of this development is seen in economic, social, and environmental aspects, where increased tourist visits can drive local economic growth, but also pose challenges in cultural and environmental preservation. This research is expected to provide recommendations for tourism developers and local government in formulating sustainable policies for dark tourism development in Sawahlunto.